If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2r + 7) = 136 Reorder the terms: 8(7 + 2r) = 136 (7 * 8 + 2r * 8) = 136 (56 + 16r) = 136 Solving 56 + 16r = 136 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + 16r = 136 + -56 Combine like terms: 56 + -56 = 0 0 + 16r = 136 + -56 16r = 136 + -56 Combine like terms: 136 + -56 = 80 16r = 80 Divide each side by '16'. r = 5 Simplifying r = 5
| 5(X-7)=20 | | b+4=16 | | .02(5000)+.03x=.025(5000+x) | | 3(9)(8)(2)= | | 52=m-52 | | 2y-(7-4y)=10y-(y-2) | | 2x-6-6-0=4 | | x+25=86 | | 4(x+18)=2(4x+2) | | y-6=5 | | 8x=7x-16 | | x+23=94 | | n-9=15 | | -4x-16=-2x+4 | | 10(x^2-x-6)=1 | | b+8=31 | | x+38=59 | | 6(y-3)+3(y+5)=51 | | 1=-X^4 | | -13-x=-5x-1 | | 0=-X^4 | | -3x-4=14 | | -3(x-6)=-x-22 | | 13=10x-x^2 | | 4-3[3-(5y-5)]=0 | | 4(2x+3)=5x+15 | | 9x-27=0 | | 7(w-4)=w+2 | | 2(3x+4)-5(1-2x)=7(2x-3)+12 | | 6a+5=9 | | 9x+-2x=42 | | 5x+7-2x=4x+9-(-10) |